To prove that the expressions \((x-5)(x+3)\) and \(2x^2 - x^2 - 2x - 20 + 5\) are equivalent, we can expand Expression 1 using the Distributive Property and simplify Expression 2.
Step 1: Expand Expression 1
Expression 1: \((x - 5)(x + 3)\)
Using the Distributive Property (also known as the FOIL method for binomials):
\[ (x - 5)(x + 3) = x \cdot x + x \cdot 3 - 5 \cdot x - 5 \cdot 3 \]
Calculating each term:
- \(x \cdot x = x^2\)
- \(x \cdot 3 = 3x\)
- \(-5 \cdot x = -5x\)
- \(-5 \cdot 3 = -15\)
Combining these terms:
\[ x^2 + 3x - 5x - 15 = x^2 - 2x - 15 \]
Step 2: Simplify Expression 2
Expression 2: \(2x^2 - x^2 - 2x - 20 + 5\)
Combining like terms:
- \(2x^2 - x^2 = x^2\)
- The linear term is \(-2x\).
- The constant terms are \(-20 + 5 = -15\).
So, we get:
\[ x^2 - 2x - 15 \]
Conclusion
Both expressions simplify to \(x^2 - 2x - 15\), therefore they are equivalent.
Answer Summary:
- Expression 1 expands to \(x^2 - 2x - 15\) using the Distributive Property.
- Expression 2 simplifies to \(x^2 - 2x - 15\) by combining like terms.
Thus, both expressions are equivalent as they yield the same polynomial.